2003
DOI: 10.1038/sj.bjc.6601372
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-7 and matrix metalloproteinase-9 are associated with unfavourable prognosis in superficial oesophageal cancer

Abstract: If oesophageal carcinoma is detected in the superficial stage, the prognosis is better than for advanced oesophageal carcinoma. But the factors which predict the prognosis and treatment policy remain unclear. Matrix metalloproteinase-7 (MMP-7) and matrix metalloproteinase-9 (MMP-9) have been reported to have close associations with tumour invasion and metastasis. In this study, we retrospectively studied the relations between MMP-7 and MMP-9 expression in immunohistochemistry, clinicopathologic factors, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 32 publications
9
59
1
1
Order By: Relevance
“…Our study as well as reports on gastrointestinal cancers showing correlation between MMP-7 and patient survival were done with an antibody against the proform of MMP-7. 33,34,38 However, according to our results, an antibody recognizing both pro and active forms gives comparable results.…”
Section: Discussionmentioning
confidence: 62%
“…Our study as well as reports on gastrointestinal cancers showing correlation between MMP-7 and patient survival were done with an antibody against the proform of MMP-7. 33,34,38 However, according to our results, an antibody recognizing both pro and active forms gives comparable results.…”
Section: Discussionmentioning
confidence: 62%
“…It has been proved that these enzymes are involved in the development of many malignant neoplasms: gastric, colorectal, pancreatic and breast cancer [40][41][42][43]. High MMP-9 protein expression in tumor tissues of EC patients has been shown in several studies [4,18,[44][45][46][47]. Percentages of MMP-9 positive immunostaining (diagnostic sensitivity) in esophageal cancer tissue reached 78% in the study by Murray et al [44] and increased with tumor stage.…”
Section: Mmp-9mentioning
confidence: 98%
“…Microvessel density in patients with highly positive staining for MMP-9 was higher than in those with negative or weak staining for MMP-9 [4], which suggests that the expression of MMP-9 possibly could offer additional information about the aggressiveness and activity of esophageal carcinoma lesions. Moreover, high expression of MMP-9 in cancer tissue may be a negative prognostic factor of EC patients' survival [45].…”
Section: Mmp-9mentioning
confidence: 99%
“…MMP activity is tightly controlled by endogenous inhibitors, including a2-macroglobulin, tissue inhibitors of metalloproteinases (TIMPs), and the membranebound inhibitor RECK (Baker et al, 2002). The expression and activity of MMPs are increased in almost every type of human cancer, and this is often associated with advanced tumor stage and poor survival (Sienel et al, 2003;Tanioka et al, 2003;Zucker and Vacirca, 2004). Recent studies demonstrated that MMPs also promote survival of cancer cells by liberating insulin growth factor and by cleavage of FAS ligand (Miyamoto et al, 2004;Strand et al, 2004).…”
Section: Introductionmentioning
confidence: 99%